Leptospirosis - Levett, Paul N. (American Society for Microbiology, 2001)
Leptospirosis is a worldwide zoonotic infection with a much greater incidence in tropical regions and has now been identified as one of the emerging infectious diseases. The epidemiology of leptospirosis has been modified by changes in animal husbandry, climate, and human behavior. Resurgent interest in leptospirosis has resulted from large outbreaks that have received significant publicity. The development of simpler, rapid assays for diagnosis has been based largely on the recognition that early initiation of antibiotic therapy is important in acute disease but also on the need for assays which can be used more widely. In this review, the complex taxonomy of leptospires, previously based on serology and recently modified by a genotypic classification, is discussed, and the clinical and epidemiological value of molecular diagnosis and typing is also evaluated.